Determination Of Correction Factor For Differential Relay Setting On Distribution Transformer Protection System Under Harmonic Condition - Nisja, Indra (2013)
In this thesis a new method is implemented to overcome the miss-operation problem of differential relay for distribution power transformer operates under harmonic condition. Correction factor as a new method to overcome this problem is introduced and implemented for the relay setting, so that the relay works properly even though operates under harmonic conditions. In order to determine the correction factor, the effects of harmonics to all components error has been obtained through laboratory test. The tests have been conducted to determine the errors that occur in power transformers and CT when operating under harmonic condition. From the error obtained, the differential current error flow through the relays was defined and differential relay setting was also determined. Experimental results for THDi ranging from 4.6% to 40.88% show that the maximum errors occurred on CT at secondary power transformers is found to be 27.21% and CT at primary power transformers is 10.12%. The maximum error occurred at power transformer found to be 8.57%. For the same THDi the correction factor which was implemented is 30.14. A relationship between THDi and differential relay setting has been established through the differential current error occurred caused by harmonic currents. Correction factor method has able to overcome the miss-operation problem of differential relay for distribution power transformer up to 40% THDi.